La proporcionalidad como instrumento de matematización en Arquímedes: un análisis a Sobre cuerpos flotantes - Mora Valbuena, Oriol; Becerra Galindo, Héctor Mauricio; Díaz Pérez, Vaianney Rocío; Bello Rivera, Cristhian Andrés (Revista Científica, 2006)
Proportionality has been fundamental in the historical development of sciences. This article stands out the role of proportionality in the processes of mathematization developed by Archimedes, specifically in his works On Floating Bodies, taken from the translation to English of Heath (1952). Particularly, of these books we will highlight the application of the proportionality: in rest, in the relationship between weight and volume, and in ideal floating bodies as the paraboloid right of revolution. Finally, we conclude that proportionality constitutes what we call mathematization instrument.